2016
DOI: 10.1097/mpg.0000000000001194
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circulating MicroRNAs in Biliary Atresia by Next‐Generation Sequencing

Abstract: Our findings indicate that patients with BA exhibit a distinct profile of circulating miRNAs and that plasma miR-140-3p may be a promising diagnostic biomarker for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
(38 reference statements)
1
16
1
Order By: Relevance
“…Peng et al [146] describe an elevated expression of miR-200a which forms part of the miR-200 cluster, confirming the finding previously reported by Zhan et al [144] in serum samples. As expected, an overexpression of miR-122-5p in plasma from BA patients was found when compared to healthy controls but not when compared to other cholestatic diseases, which suggest that miR-122 is in fact a marker of liver injury.…”
Section: Circulatory Mirnas As Biomarkers In Paediatric Liver Diseasesupporting
confidence: 79%
See 1 more Smart Citation
“…Peng et al [146] describe an elevated expression of miR-200a which forms part of the miR-200 cluster, confirming the finding previously reported by Zhan et al [144] in serum samples. As expected, an overexpression of miR-122-5p in plasma from BA patients was found when compared to healthy controls but not when compared to other cholestatic diseases, which suggest that miR-122 is in fact a marker of liver injury.…”
Section: Circulatory Mirnas As Biomarkers In Paediatric Liver Diseasesupporting
confidence: 79%
“…In fact, a recent study compared plasma miRNA profiles in children with BA [146] to healthy controls. The study consisted in of an initial “discovery” phase with nine BA patients and nine healthy controls pooled in groups of three.…”
Section: Circulatory Mirnas As Biomarkers In Paediatric Liver Diseasementioning
confidence: 99%
“…The most abundant miRNA in the liver is miR‐122, which accounts for more than half of the total hepatic miRNA content . Multiple studies have reported increased circulatory levels of miR‐122 in pediatric CLDs such as biliary atresia, CFLD, nonalcoholic fatty liver disease (NAFLD), and hepatitis B . Our study shows increased circulatory miR‐122 levels in children with CFLD when compared to both CFnoLD and healthy controls.…”
Section: Discussionmentioning
confidence: 54%
“…Interestingly, when we coupled serum MMP-7 with GGT in a composite model we obtained higher sensitivity and specificity of 97% and 94%, at optimal cut-off, which provided positive and negative predictive values of 85% and 99% if one considers the prevalence of BA of 25.9% among infants with conjugated hyperbilirubinemia (30). Other candidate biomarkers previously reported include miR-140-3p (31), miR-200b/429 (14), miR-4429, and miR-4689 (32), but with lower sensitivity (66–83%) and specificity (79–83%) and no prospective validation. In a separate study, the use of 2-dimensional gel electrophoresis with tandem mass spectrometry found a combination of 11 proteins as biomarkers; the small cohort size and relatively large number of protein analytes selected in this study limit the interpretation of the results and its potential use in clinical practice (33).…”
Section: Discussionmentioning
confidence: 97%